2019
DOI: 10.1093/aepp/ppz013
|View full text |Cite
|
Sign up to set email alerts
|

Flood Insurance and Claims: The Impact of the Community Rating System

Abstract: The Community Rating System (CRS) was introduced to encourage community-level flood mitigation and increase household-level flood insurance uptake through the National Flood Insurance Program (NFIP). Using historical data of policies-in-force and flood damage claims from 1998-2014 for all NFIP communities in Alabama and Mississippi, we estimate the relationship between community participation in the CRS and the number of policies-in-force, as well on flood damage claims. We find a significant, positive, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Multiple studies have shown a significant positive correlation between slope and flood losses [ 13 , 35 , 36 ]. The argument is that higher slopes result in greater rainfall concentration and subsequently result in faster and higher stream peaks and mean annual flows [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have shown a significant positive correlation between slope and flood losses [ 13 , 35 , 36 ]. The argument is that higher slopes result in greater rainfall concentration and subsequently result in faster and higher stream peaks and mean annual flows [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…We are not able to comment on the CRS program's effectiveness of reaching its other two goals: (1) encouraging a comprehensive approach to floodplain management and (2) reducing flood damage to insurable property. See, for example, Frimpong et al (2019), Petrolia, Landry & Coble (2013 and Burton (2015) for the positive impact CRS participation has on flood loss reduction and disaster recovery outcomes.…”
Section: Robustness Checksmentioning
confidence: 99%
“…Heeding the panel's message, this paper contributes to a group of studies evaluating the effectiveness of the CRS program in reaching its goals. Generally speaking, participation in the CRS program is associated with greater insurance penetration rates, fewer flood damages and better disaster recovery outcomes (Burton 2015, Highfield & Brody 2017, Frimpong, Petrolia, Harri & Cartwright 2019. A 2006 RAND report provided evidence that insurance penetration rates are higher amongst CRS communities only because of lower insurance prices and not because of the CRS activities themselves (Dixon, Clancy, Seabury & Overton 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Flood insurance premium rates are determined mainly by Flood Insurance Rate Maps (FIRMs) which are updated periodically. Other factors that affect premiums include whether the structure is elevated above historic flood levels and the extent to which the community participates in the community rating system (Frimpong et al, 2020). As such, the assessed flood risk level for a structure can change when new FIRMs take effect.…”
Section: National Flood Insurance Programmentioning
confidence: 99%